ШЕЪРИЯТДА ТАСВИР ВА ТАСАВВУР УЙҒУНЛИГИ - Матякупов, С. (SCIENCE and SOCIETY, 2019)
The article deals with the issues of spiritual world and artistic description in the Uzbek poetry. There are given different points of view about authors’ skill on the basis of the analysis of the examples from the works of A.Aripov and J.Kamal.